The conjuring - Wan, James, 1977-; Farmiga, Vera; Wilson, Patrick, 1973-; Livingston, Ron; Bishara, Joseph (Burbank, CA : Warner Bros. Entertainment, 2013)
Two paranormal investigators work to help a family being terrorized by a dark presence.
Originally released as a motion picture in 2013.
Dolby digital 5.1, anamorphic wide screen 1.77:1.
Features: Scaring the "@$*%" out of you, UltraViolet digital copy of the film.
Camera, John R. Leonetti ; editor, Kirk Morri ; music, Joseph Bishara.
Vera Farmiga, Patrick Wilson, Ron Livingston, Lili Taylor, Joey King, Shanley Caswell, Haley McFarland, Mackenzie Foy.
MPAA rating: R.
Keywords: Ghost plays; Supernatural -- Drama; Haunted houses -- Drama; Ghost films; Fiction films; Video recordings for the hearing impaired; Thriller films; Feature films; Horror films